2016
DOI: 10.1508/cytologia.81.423
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of Gemcitabine-Loaded-Microemulsion (Isopropyl Myristate/Tween 80/Span 20/Water/Ethanol) on A549 Non-Small Cell Lung Cancer Cells

Abstract: Summary Gemcitabine (GEM) is a chemotherapeutic agent with several dose limitation aspects. It was encapsulated in three microemulsion (ME) formulations with nanoparticles that differ in polarity: hydrophilic MEa, hydrophobic MEb and relatively neutral MEc. The apoptotic effect of the ME formulations was evaluated in the A549 non-small cell lung cancer cells, whereas the side effects of the formulas on the healthy cells were tested in the HFS human foreskin cells. The cell toxicity of all GEM-loaded-MEs (MEa+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, other compounds found among SA extracts in this work (Table 2) including heneicosane, hexadecanoic acid, ethyl ester, lupeol were found to be cytotoxic to HEp-2 (larynx), MCF-7 (breast) and NCI-H292 (lung) cancer cells (Bastos et al, 2017). Isopropyl myristate was cytotoxic to A549 lung cancer cells (Alkhatib and Alkhayyal, 2016). γ-Sitosterol was cytotoxic to A549 (lung) and MCF-7 (breast) (Sundarraj et al, 2012).…”
Section: Effects On Apoptotic Gene Expressionsmentioning
confidence: 59%
“…In addition, other compounds found among SA extracts in this work (Table 2) including heneicosane, hexadecanoic acid, ethyl ester, lupeol were found to be cytotoxic to HEp-2 (larynx), MCF-7 (breast) and NCI-H292 (lung) cancer cells (Bastos et al, 2017). Isopropyl myristate was cytotoxic to A549 lung cancer cells (Alkhatib and Alkhayyal, 2016). γ-Sitosterol was cytotoxic to A549 (lung) and MCF-7 (breast) (Sundarraj et al, 2012).…”
Section: Effects On Apoptotic Gene Expressionsmentioning
confidence: 59%
“…Therefore, it can be concluded that due to the large amounts of intracellular damage induced by NE-DTX+TQ, the T47D cells respond by activating autophagy with subsequent apoptosis signaling pathways. 31 Taken together, the data suggest that the improved antiproliferative effect of NE-DTX+TQ can be attributed to the triggering of various molecular cascades involved in the cell death mechanisms. 32 Previous studies have reported similar findings regarding the activation of apoptosis simultaneously with autophagy for the nano-delivery system in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 88%
“…The growth of the MCF-7 cells was greatly impeded when subjected into the LEM-IFO meanwhile SAL-IFO has the best inhibition effect on the growth of the HeLa cells. The great apoptotic effect of LEM-IFO on the MCF-7 cells may stem from the extracellular vesicle formation, seen under the light microscope, indicating that LEM-IFO has got attached into the cell membrane and induced apoptosis integrated with autophagocytosis 22 . In contrast, the light microscopy images revealed that the apoptotic effect of SAL-IFO on the HeLa cells has enlarged the cancer cells and damaged the nucleus without vesicle formation which implies that SAL-IFO has passed the cell membrane.…”
Section: Discussionmentioning
confidence: 99%